How technology can help in teaching listening - Cherednichenko, Galina; Kunytsia, Lyudmila; Shapran, Ludmila (My University, 2007)
In the article authors describe the role of electronic media in education and how such technologies can help in teaching listening.
Keywords: технологія; technology; аудіювання; teaching listening; кафедра ділової іноземної мови та міжнародної комунікації